Antibodies against hepatitis C virus in hemodialysis patients - Refik MAS,; Selim NALBANT,; Yavuz SAYKAL,; Ümit ATEŞKAN,; Ayhan DİNÇ,; Tahir ÜNAL,; Fikri KOCABALKAN, (Turkish Journal of Gastroenterology, 2019)
-